Network Design Using Proxy-Based BGP (Border Gateway Protocol) Routing - A.R. Walad Mahfuzhi; Yuza Reswan; Kurnia Marga Handayani (Penerbit Jurnal Indonesia, 2024)
Today, information technology is increasingly advanced and developing rapidly, providing many benefits and conveniences in various fields. Mikrotik improves the stability of the internet network. In addition, XYZ Bengkulu City uses the internet network. The routing configuration on the router used changes from static routing done manually to dynamic routing BGP (Border Gateway Protocol). BGP is a type of routing protocol used to transmit information between autonomous systems. The purpose of the researcher is to design and build an internet network for XYZ Bengkulu City using BGP so that the move from the main line to the backup line is carried out automatically with BGP Route. Continued by checking the quality of both lines using the QoS (Quality of Service) method, some of the QoS parameters used as a reference are throughput, delay, jitter and packet loss, by following the QoS standard from TIPHON. So in this study, we conducted tests and discussions that focused more on how routing using BGP could work well, automatically backing up internet connections and analyzing QoS as a result of the research that BGP routing works well and has an optimal internet connection for operational use of XYZ Bengkulu City